Validity and reliability of the Activity Card Sort - Hong Kong version. - Chan, V.; Chung, J.; Packer, Tanya (Slack Incorporated, 2006)
It is pertinent for occupational therapists to measure the changing patterns of activity engagement of older adults who might have undergone the process of aging, institutionalization, and illness. The Activity Card Sort was developed to measure the level of activity engagement in the main areas of occupational performance. This study examined the reliability, internal consistency, and construct validity of the Hong Kong version of the Activity Card Sort. Using expert panel reviews, 65 activities were identified as culturally appropriate for inclusion in the Hong Kong version. Sixty geriatric clients who had experienced a stroke participated in the evaluation. Results showed that the Hong Kong version of the Activity Card Sort was able to discriminate between clients with different levels of functioning (t = -14.24; p = .00), and was positively associated with the Comprehensive Quality of Life Scale (r = 0.86; p = .00). Excellent test-retest reliability (r = 0.98) and internal consistency (r = 0.89) were demonstrated. The findings suggest the Hong Kong version of the Activity Card Sort is a reliable and valid instrument to use with the Hong Kong Chinese elderly population